Rose's biomedical governance in Puenzo’s Wakolda - Sharma, Pradip (Rainbow : Journal of Literature, Linguistics and Culture Studies, 2025)
This study explores biomedical intervention in Lilith’s growth deficiency as depicted in Lucía Puenzo’s Wakolda, drawing parallels to Nazi medical experiments and Argentina’s post-war complicity. The novel follows José, a former Nazi doctor who continues unethical experiments on women and children while in hiding. Using Nikolas Rose’s theory of molecular biopolitics, the analysis examines how José’s treatments—protein supplements for pregnant Eva and growth hormone injections for Lilith—reflect broader mechanisms of biopolitical control. Rose argues that biotechnology reduces the body to molecular material, subject to political, medical, and social regulation. José’s manipulation of Lilith’s biology symbolically echoes Argentina’s efforts to exploit Nazi expertise for national gain. The study also critiques Eva’s passive role in exposing her family to medical manipulation, emphasizing the dangers of uncritical trust in biomedical authority. Ultimately, the paper warns against the misuse of biomedicine and highlights the need to protect human dignity from exploitative scientific agendas.